Serum Calcium Levels in Preterm and Term Neonates on Phototherapy - Arora, S; Narang, GS; Singh, G (Journal of Nepal Paediatric Society, 2014)
Introduction: In addition to known causes of hypocalcemia like, prematurity, Intrauterine growth retardation (IUGR), asphyxia, sepsis, infants of diabetic mothers (IDM), high phosphate formula, Magnesium deficiency, effect of phototherapy on serum calcium levels has caught attention of researchers from time to time. The objectives of this study were to evaluate serum calcium levels in relation to duration of phototherapy, single surface Vs double surface phototherapy in term and preterm neonates. Materials and Methods: This study was done in a neonatal ICU of a tertiary care hospital. Hundred preterm and term neonates > 72 hrs of age with weight appropriate for gestational age were selected. Serum calcium levels were measured at the onset and after 24 hrs and 48 hrs of phototherapy and results were analyzed in both the groups. Results: Hypocalcemia was more frequently observed in term group as compared to preterm group. Hypocalcemia occurred more frequently after 48 hrs of continuous phototherapy in both groups. Hypocalcemia was more common under DSPT as compared to SSPT in both groups. Conclusion: Hypocalcemia is a significant problem in neonates subjected to phototherapy. DOI: http://dx.doi.org/10.3126/jnps.v34i1.9165 J Nepal Paediatr Soc 2014;34(1):24-28